Antimicrobial resistance in coagulase-negative staphylococci isolated from subclinical mastitis in Ettawa Crossbred goat (PE) in Yogyakarta, Indonesia - widodo suwito; WIDAGDO SRI NUGROHO; AGNESIA ENDANG TRI HASTUTI WAHYUNI; BAMBANG SUMIARTO (Society for Indonesian Biodiversity, 2021)
Abstract. Suwito W, Nugroho WS, Wahyuni AETH, Sumiarto B. 2021. Antimicrobial resistance in coagulase-negative staphylococci isolated from subclinical mastitis in Ettawa Crossbred goat (PE) in Yogyakarta, Indonesia. Biodiversitas 22: 3418-3422. Subclinical mastitis (SCM) in Ettawa Crossbred Goat (PE) is most frequently caused by staphylococci with a significant reduction in milk yield. The aim of this study is to determine antimicrobial resistance patterns of coagulase-negative staphylococci (CoNS) from PE goat SCM. A total of 36 CoNS isolates originating from PE goat SCM were collected in semisolid tube use in this study. All CoNS isolates were further examined for antimicrobial susceptibility testing by the Kirby-Bauer disc diffusion method. Antibiotic susceptibility of CoNS isolated samples according to Clinical Laboratory Standards Institute (CLSI). The CoNS isolates showed the highest resistance rate against sulfamethoxazole (65%), ampicillin (55.56%), penicillin (45%), cefoxitin (33.33%), erythromycin (25%), oxytetracycline (20%), tetracycline (15%), gentamicin and neomycin (11.11%), while oxacillin was sensitive. The highest of multiple antimicrobials resistance observed 15% in ampicillin, penicillin and tetracycline, then 5-10% in ampicillin, penicillin, erythromycin, tetracycline and oxytetracycline. The majority of CoNS in this study were resistant to sulfamethoxazole and then, followed by ampicillin, penicillin, cefoxitin, erythromycin, oxytetracycline, tetracycline, gentamicin and neomycin. In addition, most isolates were penicillin-resistant and multidrug-resistant (MDR).